Tunisia : Fourth Review Under the Stand-by Arrangement and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report, 2014)
EXECUTIVE SUMMARY Context. On June 7, 2013, the Executive Board approved a 24-month Stand-By Arrangement in an amount equivalent to 400 percent of quota (SDR 1.146 billion or about USD 1.75 billion). To date, SDR 573 million equivalent to USD 877 million has been disbursed. The pillars of the program are to: (i) achieve short-term macroeconomic stability; (ii) lay the foundation for stronger and more inclusive growth; and (iii) protect the most vulnerable. Background. Progress in the political transition is leading to increased donor support this year, including from regional partners. On the economic front, growth remains timid, headline inflation has increased, and rising external imbalances have continued to put pressure on foreign reserves. Program implementation has been satisfactory. All quantitative performance criteria have been met. On the structural reform agenda, the authorities have made up for some key delays in areas that include reforming public banks, setting up a household support program, and the tax administration modernization agenda. Program strategy. Prudent fiscal policy, tighter monetary policy, and greater exchange rate flexibility need to be sustained and intensified to contain high external and fiscal deficits, anchor inflationary expectations, and bolster the still lackluster investors' confidence. Important steps have been taken to strengthen the financial system, notably with the design of public bank restructuring plans, but implementation will be key. Progress on structural reforms-in particular, to improve the business climate-is critical for improving the conditions for private sector-led and inclusive growth. Risks to program implementation are important. Main risks relate to regional and domestic security tensions, setbacks in the political transition, and weaker economic activity in major trading partners. The implementation of program policies will continue to be tested by a difficult social environment and opposition from vested interests. The completion of the fourth review will make SDR 143.25 million (about USD 220 million) available.